PENGARUH KOMPENSASI, KOMITMEN ORGANISASIONAL, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi pada PT Teduh Makmur Semarang) - Dewi, Safrianisa; Rahardjo, Mudji (Faculty of Economics and Business Diponegoro University, 2015)
The purpose of this research is to explain how the variable of compensation,organizational commitment, and organizational culture influence to PT. Teduh Makmur Semarang employee performance. The data of this research were collected through a questionnaire distributed to 43 employees of PT. Teduh Makmur Semarang. This research used a saturated or census sampling method. The analysis method used is multiple linear regression.The result of this research shows that compensation, organizational commitment, and organizational culture influence positively and significantly to the employee performance. Variable used in this research give positive response, meaning that the compensation, organizational commitment, and organizational culture improving the performance of PT. Teduh Makmur Semarang employee. Value of determination coefficient or R2 is 0,712, which means employee performance is affected by compensation, organizational commitment, and organizational culture amounted to 71,2%.Based on statistical data analysis, found that most influential variable is thee variable of organizational commitment of 0,454, while the least influential variable is the variable of compensation of 0,393.